Invasive Candida Infections in Liver Transplant Recipients: Clinical Features and Risk Factors for Mortality. Issue 5 (May 2017) - Bassetti, Matteo; Peghin, Maddalena; Carnelutti, Alessia; Righi, Elda; Merelli, Maria; Ansaldi, Filippo; Trucchi, Cecilia; Alicino, Cristiano; Sartor, Assunta; Wauters, Joost; Lagrou, Katrien; Tascini, Carlo; et al.
Abstract : Background: Invasive fungal infections remain a leading cause of morbidity and mortality among liver transplant recipients (LTRs). In this patient population, invasive Candida infections (ICIs) account for the large majority of cases. To date, only small studies and case-series analysing clinical presentation and risk factors for mortality in LTRs with ICIs are available. Methods: We performed a retrospective multicenter multinational study in 10 centers in Europe and Brazil. All consecutive LTRs developing ICIs during the period January 2011 to December 2013 were included in the study. Results: A total of 42 LTRs were included. Median age was 52.5 years, and 78.6% of patients were men. Viral hepatitis was the most common cause for liver transplantation (42.9%). Candidemia represented the majority of cases (24, 57.1%), followed by intra-abdominal candidiasis (18, 42.9%). Overall 30-day mortality was 23.8%, with higher mortality in patients with candidemia compared with intra-abdominal candidiasis (37.5% vs 5.6%, P = 0.02). Multivariate analysis showed candidemia to be a risk factor associated with mortality among LTRs presenting ICIs (odds ratio, 11.86; 95% confidence interval, 1.5-280; P = 0.01). Candida albicans represented the most common isolate (59.5%). High rates of antifungal resistances were found, with 16.7% and 4.8% of isolates displaying resistance to azoles and caspofungin, respectively. Conclusions: Our study confirms the occurrence of high mortality rates in LTRs developing ICIs. Mortality rates varied according to the type of infection, with candidemia representing a risk factor for mortality. The high rates of antifungal resistance should be considered in the choice of the empiric antifungal regimen. Abstract : Supplemental digital content is available in the text.